Incidence and predictors of recurrent acute coronary syndrome among adult patients with acute coronary syndrome in West Amhara, Ethiopia: a multicenter retrospective follow-up study - Alamaw, Addis Wondmagegn; Asefa, Tseganesh; Abebe, Gebremeskel Kibret; Zemariam, Alemu Birara; Liyew, Bikis (Frontiers in Cardiovascular Medicine, 2023)
Introduction Acute coronary syndrome (ACS) is the most common cause of morbidity and mortality in patients with coronary heart disease. Furthermore, the recurrence of this problem has significant adverse outcomes. However, there is insufficient information pertaining to this problem in Ethiopia; hence, this study aims to assess the incidence rate and identify the predictors of ACS recurrence in the West Amhara region. Methods A retrospective follow-up study was conducted among 469 patients diagnosed with primary ACS. Data from the patient chart were collected using a pre-tested structured data extraction tool. The study employed the Weibull regression analysis model, and the effect size was measured using an adjusted hazard ratio (HR) with a 95% confidence interval (CI). The statistical significance of the findings was established based on a p-value <0.05. Result A total of 429 patients were included in the final analysis [average age, 60 ± 13.9 years; and 245 (57.1%) men]. A total of 53 patients (12.35%; 95% CI: 9.55%–15.83%) experienced recurrent ACS. The overall risk time was found to be 93,914 days (3,130.47 months), and the recurrence rate was 17/1,000 patients/month. The identified predictors were the typical symptoms of ACS such as syncope (HR: 3.54, p = 0.013), fatigue (HR: 5.23, p < 0.001), history of chronic kidney disease (HR: 8.22, p < 0.001), left ventricular ejection fraction of <40% (HR: 2.34, p = 0.009), not taking in-hospital treatments [aspirin (HR: 9.22, p < 0.001), clopidogrel (HR: 4.11, p = 0.001), statins (HR: 2.74, p = 0.012)], and medication at discharge [statins (HR: 4.56, p < 0.001)]. Conclusion This study found a higher incidence rate of recurrent ACS. Hence, the implementation of guideline-recommended anti-ischemic treatment should be strengthened.